Effects of guanidinoacetic acid on gene expression in adipose tissue of broiler chickens: a differential expression analysis based on small RNA sequencing - Liu, Mengqian; Ruan, Jinrui; Yang, Yu; Li, Mengyuan; Gu, Zifu; Ge, Changrong; Cao, Weina (Frontiers in Veterinary Science, 2026)
This study aims to elucidate the mechanism by which guanidinoacetic acid (GAA) reduces abdominal fat deposition in broilers, focusing on the regulatory role of microRNAs (miRNAs). Excessive fat accumulation in the abdomen is a common issue in meat-type chickens as it reduces feed efficiency and compromises meat quality. By performing small RNA (sRNA) sequencing and analysis on broilers from GAA-treated and control groups, a total of 46 differentially expressed miRNAs were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that these miRNAs were significantly enriched in pathways related to lipid metabolism. Further investigation revealed that GAA likely reduces fat deposition and promotes lipid oxidation by up-regulating gga-miR-103-3p and gga-miR-107-3p, thereby inhibiting their target genes, stearoyl-CoA desaturase (SCD) and transmembrane protein 35B (TMEM35B). These findings provide a theoretical foundation for the application of GAA to improve growth performance and meat quality in broilers.